Pengaruh Karakteristik Individu Dan Leadership, Terhadap Kinerja Organisasi Dengan Teamwork Sebagai Variabel Intervening Pada Puskesmas Terakreditasi Paripurna Di Kabupaten Pasuruan - Mira Kurniawati; Lidia Andiani; Hanif Mauludin (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
Background - Based on the observations of researchers while being an accreditation companion at a fully accredited health center, several components of the success of the puskesmas in getting accreditation need to be studied so that they can be applied in other Puskesmas scopes. Purpose – This study aims to examine and analyze the effect of individual characteristics and leadership skill on organizational performance with Teamwork as an intervening variable at accredited Community Health Centers in Pasuruan district. Design/ Methodology/ ApproachThis study examines the effect of individual characteristic and leadership skill on organizational performance with Teamwork skill as an intervening variable at plenary accredited Community Health Center in Pasuruan district. The sample of this study are employees who involved in accreditation process and quality improvement at two plenary accredited Community Health Centers totaling 157 people. Hypothesis testing used Structural Equation Modelling with Partial Least Square regression. Result and Discussion – The result of this study shows that individual characteristics and leadership skill have significant positive effect toward Teamwork skill. Individual characteristic and leadership skill also have significant positive effect toward organizational performance through Teamwork which means that improvement on individual characteristic and Teamwork skill lead to better organizational performance along with better Teamwork skill. Leadership variable dominantly affects organizational performance through Teamwork skill rather than individual characteristic. Leadership is second order variable with transformational leadership which has dominant measurement toward leadership skill rather than transactional leadership. Conclusion –The result of this study shows that there is positive and significant effect between individual characteristic and leadership skill toward organizational performance with Teamwork skill as an intervening variable. Leadership skill dominantly affects organizational performance through Teamwork rather than individual characteristic. Leadership is second order variable with transformational leadership dimension which has more dominant effect toward leadership skill rather than transactional leadership. Research Implication – This research has implications for assessing individual characteristics and leadership, as well as Teamwork on the organizational performance of the health center.